2013
DOI: 10.2174/156720513804871480
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Enzyme Processivity Mediates Differential Aβ Production by PS1 and PS2

Abstract: The γ-secretase complex cleaves the carboxy-terminal 99 residue (C99) fragment of the amyloid precursor protein (APP) to generate the amyloid-β (Aβ) peptide. The catalytic activity of this complex is mediated either by the presenilin-1 (PS1) or the presenilin-2 (PS2) subunit. In vitro and in vivo studies have demonstrated that PS1-containing complexes generate more total Aβ product than PS2-containing complexes, indicating greater cleavage activity by PS1-containing γ-secretase complexes at the APP γ-site. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Several studies have reported a lower activity of PS2 γ‐secretases compared to PS1 γ‐secretases . Our work confirms, both in single‐KO and rescued cells, that APP substrates are more efficiently processed by PS1 than by PS2 and this is in line with published results showing a predominant implication of PS1 in the γ‐secretase activity . However, we observed that PS2‐expressing cells still efficiently cleave C99‐GVP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have reported a lower activity of PS2 γ‐secretases compared to PS1 γ‐secretases . Our work confirms, both in single‐KO and rescued cells, that APP substrates are more efficiently processed by PS1 than by PS2 and this is in line with published results showing a predominant implication of PS1 in the γ‐secretase activity . However, we observed that PS2‐expressing cells still efficiently cleave C99‐GVP.…”
Section: Discussionsupporting
confidence: 92%
“…Absence of PS1 (PS1KO) provokes a drastic reduction of APP and Notch cleavages, which are restored by the expression of human PS1 (rPS1wt). These observations are consistent with previously published data [21,22] underlining the predominant role of PS1 in c-secretase-dependent substrate processing. Strikingly, our results further indicate that pharmacological c-secretase inhibitors differently affect PS1 and PS2 c-secretases.…”
Section: Introductionsupporting
confidence: 93%
“…However, mice lacking both PS1 and PS2 die much earlier than PS1 KO mice (Donoviel et al, 1999), and the neurogenesis defects in PS1/PS2-null neural progenitor cells (NPCs) are much more severe than those in PS1-deficient NPCs (Handler et al, 2000;Hitoshi et al, 2002;Kim and Shen, 2008). In terms of Aβ generation, PS1 and PS2 exhibit different properties in nonneuronal cells and/or nonhuman experimental systems, most of which express exogenous PS, and PS2/γsecretase shows less total proteolytic activity than PS1/γ-secretase (Lai et al, 2003;Yonemura et al, 2011;A. Pintchovski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed the absence of any signi cant change in the processing of C99 or the release of Aβ when cells have a nearly 50% reduction of PS1 protein levels. This was rather surprising regarding the previous reports on the preponderant importance of PS1 for γ-secretase substrates cleavage and overall Aβ production [33][34][35][36][37]. One can imagine, as mentioned above, that the reduction of PS1 protein levels is not signi cant enough to observe any effect.…”
Section: Discussionmentioning
confidence: 87%
“…A recent cryo-EM study revealed a similar structure and conformational state between both presenilins (PSs), suggesting similar catalytic activities, but differences in their membraneanchoring motifs [32]. We and others have repeatedly shown a major contribution of PS1 to Aβ production intended as substrate cleavage [33][34][35][36][37], rendering the exact role of PS2 in the amyloid pathology less understood, and in turn PS2 less attractive as a therapeutic target. However, more recent ndings revealed the enrichment of PS2 γ-secretases in endosomal compartments, which might explain its lesser overall contribution to substrate cleavage simply by secondary encounters; substrates such as APP and its CTFs are indeed likely to be e ciently processed in cells rst along tra cking through the secretory pathway and at the plasma membrane before reaching the endosomal pathway [38].…”
Section: Introductionmentioning
confidence: 99%